Enhanced Urea Production in the Diazotroph Azotobacter vinelandii as a Means of Stable Nitrogen Biofertiliser Production - Brett M. Barney; Benjamin R. Dietz (Microbial Biotechnology, 2025)
ABSTRACT Diazotrophic microbes capture atmospheric nitrogen and convert it into ammonia using the enzyme nitrogenase in a process that provides much of the fixed nitrogen that is required to sustain life in the biosphere. The advent of the Haber Bosch industrial process in the 20th century ushered in an age when agricultural productivity could circumvent the constraints of biological nitrogen fixation, leading to higher productivity based on chemical fertilisers. This industrial process now provides a substantial amount of the nitrogen that we apply to crops, but comes with a large environmental and economic cost. In contrast, biological nitrogen fixation still contributes nitrogen to crops and has the potential to displace some of the industrial nitrogen if we can engineer methods to increase nitrogen levels that are provided to the plant or develop stronger associations between diazotrophs and nonlegume plants. Many of the processes scientists have employed to enhance the nitrogen production by diazotrophs to develop improved biofertilisers have focused on delivering nitrogen in the form of ammonium. In this report, we describe an alternative approach that provides the nitrogen as urea in the form of a terminal product. Using the model diazotroph Azotobacter vinelandii and a three‐step approach that deletes the native urease, incorporates a functional arginase and overcomes the feedback inhibition of the arginine biosynthesis pathway, we have increased levels of urea that could be obtained from previous approaches by approximately 43‐fold. Our results demonstrate the ability to support the growth of a green alga with these engineered strains and yield total extracellular nitrogen that is comparable to what has been achieved with ammonium.